PENGEMBANGAN MEDIA FLASH PADA PENGENALAN KOSAKATA DALAM CERITA RAKYAT JEPANG â€œSARU KANI KASSENâ€ - CINTIAPUTRI, RESTY (HIKARI, 2020)
Abstract Literature is a familiar thing for language learners. Likewise for Japanese language learners, studying a literary work can increase vocabulary to understand a work. However, literary learning is not taught at school. Teaching literature is important to teach, to support language skills. One of Japanese literary works is folklore. The saru kani kassen folklore is one of the most well-known stories in Japan. Flash media are media that contain animated